POWER SPECTRAL DENSITY (PSD) ANALYSIS OF ELECTROENCEPHALOGRAPHY (EEG) SIGNALS FROM COGNITIVE LISTENING TEST RESULTS IN MALE SUBJECTS - Nur Sakinah, Feby
Cognitive abilities are abilities related to thinking processes which development varies greatly in each human being. This study aims to analyze the Power Spectral Density (PSD) of brain waves generated from cognitive listening tests by determining which hemisphere is more active and the changes in alpha frequency. This study uses a wireless electroencephalograph (EEG) with (14 + 2) electrodes to obtain record of the difference in brain wave potential versus time at each electrode. Subjects were 11 male students who had normal hearing and no history of neurological disease. Subjects were given cognitive test questions by means of a hearing test with a duration of 17 minutes. The obtained Data measurements is within (.edf) format and then processed with EEGlab and BioSig produce data with the (.set) format. By using MATLAB, the data was processed by centering, filtering and Periodogram Welch to get the PSD value. The results of data processing are presented in tables and graph. Based on the result, the condition while close eyes give the higher PSD value than open eyes condition. It can be conclude that, there have a different alpha frequency value after and before do the test and the dominan hemisphere active during the test is right hemisphere.